A Portable Biofiltration System Utilizing Local Organic Waste for Rainwater Treatment - Eka Apriliasi; Nur Hakim; Verdy Ananda Upa; Muhammad Naufal; Rizal Firdaus (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2026)
Low rainwater collection in some campus areas of the Indonesian Institute of Technology campus creates unnecessary surface runoff and high municipal water usage. Rainwater coming from roofs was not treated and sent directly to drainage channels. A community service program was carried out to offer an alternative solution by producing a portable biofiltration system made of local organic material as the filter media. Implementation of the program was done in multiple steps, which included: examination of partner needs, technical system design phase, physical device construction and production, installation on-site at the fielding location, initial operational testing, and user support. The system that had been created is intended to be straightforward, mobile, and low-maintenance, making it possible for its use to go beyond just the campus setting. Depending on design specifications and regional rainfall patterns, the system can handle roughly 100 to 300 liters of rainwater with each rainfall, decreasing surface runoff by approximately 20 to 35 percent, and providing about 15 to 25 percent of the non-drinkable water needs in the nearby region. The findings suggest that using suitable technology made from local resources can promote sustainable water management and raise awareness about rainwater use within the educational community.